Reconstitution of Mycobacterium marinum Nonhomologous DNA End Joining Pathway in Leishmania - Wen-Wei Zhang; Douglas G. Wright; Lynn Harrison; Greg Matlashewski (mSphere, 2022)
ABSTRACT In mammalian cells, DNA double-strand breaks (DSBs) are mainly repaired by nonhomologous end joining (NHEJ) pathway. Ku (a heterodimer formed by Ku70 and Ku80 proteins) and DNA ligase IV are the core NHEJ factors. Ku could also be involved in other cellular processes, including telomere length regulation, DNA replication, transcription, and translation control. Leishmania, an early branching eukaryote and the causative agent of leishmaniasis, has no functional NHEJ pathway due to its lack of DNA ligase IV and other NHEJ factors but retains Ku70 and Ku80 proteins. In this study, we generated Leishmania donovani Ku70 disruption mutants and Ku70 and Ku80 double gene (Ku70/80) disruption mutants. We found that Leishmania Ku is still involved in DSB repair, possibly through its binding to DNA ends to block and slowdown 5′ end resections and Ku-Ku or other protein interactions. Depending on location of a DSB between the direct repeat genomic sequences, Leishmania Ku could have an inhibiting effect, no effect or a promoting effect on the DSB repair mediated by single strand annealing (SSA), the most frequently used DSB repair pathway in Leishmania. Ku70/80 proteins are also required for the healthy proliferation of Leishmania cells. Interestingly, unlike in Trypanosoma brucei and L. mexicana, Ku70/80 proteins are dispensable for maintaining the normal lengths of telomeres in L. donovani. We also show it is possible to reconstitute the two components (Ku and Ligase D) NHEJ pathway derived from Mycobacterium marinum in Leishmania. This improved DSB repair fidelity and efficiency in Leishmania and sets up an example that the bacterial NHEJ pathway can be successfully reconstructed in an NHEJ-deficient eukaryotic parasite. IMPORTANCE Nonhomologous end joining (NHEJ) is the most efficient double-stranded DNA break (DSB) repair pathway in mammalian cells. In contrast, the protozoan parasite Leishmania has no functional NHEJ pathway but retains the core NHEJ factors of Ku70 and Ku80 proteins. In this study, we found that Leishmania Ku heterodimers are still participating in DSB repair possibly through blocking 5′ end resections and Ku-Ku protein interactions. Depending on the DSB location, Ku could have an inhibiting or promoting effect on DSB repair mediated by the single-strand annealing repair pathway. Ku is also required for the normal growth of the parasite but surprisingly dispensable for maintaining the telomere lengths. Further, we show it is possible to introduce Mycobacterium marinum NHEJ pathway into Leishmania. Understanding DSB repair mechanisms of Leishmania may improve the CRISPR gene targeting specificity and efficiency and help identify new drug targets for this important human parasite.